Multi-omics analysis of SFTS virus infection in Rhipicephalus microplus cells reveals antiviral tick factors - Petit, Marine J.; Flory, Charlotte; Gu, Quan; Fares, Mazigh; Lamont, Douglas; Score, Alan; Davies, Kelsey; Bell-Sakyi, Lesley; Scaturro, Pietro; Brennan, Benjamin; Kohl, Alain (Nature communications, 2025)
The increasing prevalence of tick-borne arboviral infections worldwide necessitates advanced control strategies, particularly those targeting vectors, to mitigate the disease burden. However, the cellular interactions between arboviruses and ticks, especially for negative-strand RNA viruses, remain largely unexplored. Here, we employ a proteomics informed by transcriptomics approach to elucidate the cellular response of the Rhipicephalus microplus -derived BME/CTVM6 cell line to severe fever with thrombocytopenia syndrome virus (SFTSV) infection. We generate the de novo transcriptomes and proteomes of SFTSV- and mock-infected tick cells, identifying key host responses and regulatory pathways. Additionally, interactome analysis of the viral nucleoprotein (N) integrated host responses with viral replication and dsRNA-mediated gene silencing screen reveals two anti-SFTSV effectors: the N interacting RNA helicases DHX9 and UPF1. Collectively, our results provide insights into the antiviral responses of R. microplus vector cells and highlight critical SFTSV restriction factors, while enriching transcriptomic and proteomic resources for future research. Severe Fever with Thrombocytopenia Syndrome Virus (SFTSV) is a deadly tick-borne virus and a growing global health threat. In this study, Petit et al. used a multi-omics approach on SFTSV-infected tick cells to study its impact and reveal host antiviral responses and key restriction factors.